Promoting Collaboration in InFleX Modality: A Case on Teaching History of Mathematics - Medina, Joneil Bariñan (Universitas Islam Negeri Sunan Kudus, 2023)
The goal of mathematics education in the Philippines is the development of critical thinking and problem-solving skills of the students. The pandemic, however, posed a serious challenge in implementing strategies that would promote 21st-century skills among unprepared students. This paper aimed to present the mathematics instructor’s experience in promoting collaboration in the time of the pandemic among pre-service teachers, utilizing the innovative and flexible (InFleX) modality. As action research, this paper describes the implementation of modular collaboration projects and study groups to promote collaboration. Utilizing local research outputs on interdisciplinary contextualized project-based units, collaborative problem solving, and communication patterns, these mechanisms of implementing collaborative activities in online and distance learning modality was devised. Purposive sampling is employed in the collection of student data. Preliminary survey results of the student experiences yielded some types of students’ mechanisms of decision-making and collaboration that are termed additive; goal-oriented and consultative. Students also expressed the role of the teacher in the collaboration activity and the challenges encountered. The implementation of the modular collab projects amidst the challenge of connectivity and the pandemic through the establishment of study groups and multiple communication channels encouraged students to achieve the module outcomes. Tujuan pendidikan matematika di Filipina adalah pengembangan kemampuan berpikir kritis dan pemecahan masalah para mahasiswa. Namun, pandemi menimbulkan tantangan serius dalam menerapkan strategi yang akan mempromosikan keterampilan abad ke-21 di kalangan mahasiswa yang tidak siap. Artikel ini bertujuan untuk menyajikan pengalaman instruktur matematika dalam mempromosikan kolaborasi di masa pandemi di antara calon guru, dengan memanfaatkan modalitas inovatif dan fleksibel (InFleX). Sebagai penelitian tindakan, artikel ini menjelaskan implementasi proyek kolaborasi modular dan kelompok belajar untuk mempromosikan kolaborasi. Memanfaatkan hasil penelitian lokal pada unit berbasis proyek kontekstual interdisipliner, pemecahan masalah kolaboratif, dan pola komunikasi, mekanisme pelaksanaan kegiatan kolaboratif dalam modalitas pembelajaran online dan jarak jauh ini dirancang. Purposive sampling digunakan dalam pengumpulan data mahasiswa. Hasil survei awal dari pengalaman mahasiswa menghasilkan beberapa jenis mekanisme pengambilan keputusan dan kolaborasi mahasiswa yang disebut aditif; berorientasi pada tujuan dan konsultatif. Mahasiswa juga mengungkapkan peran guru dalam kegiatan kolaborasi dan tantangan yang dihadapi. Implementasi proyek kolaborasi modular di tengah tantangan konektivitas dan pandemi melalui pembentukan kelompok belajar dan berbagai saluran komunikasi mendorong mahasiswa untuk mencapai hasil modul.